Career development intervention module: towards enhancing unskilled workers in Malaysia - Adanan, Mona Adlina; Mohd Rasdi, Roziah; Ismail, Asmah (Innovative Journal, 2021)
This study validated and tested the reliability of Career Development Intervention Module (CDIM) meant for unskilled workers within the context of Malaysia. The module was developed based on Intelligent Career Model (ICM), with incorporation of Sidek’s Module Development Model (SMDM) at the time of the development process. The content validity of the developed module was determined by gaining feedback from a panel of five experts during the module development phase. The reliability test was performed via pilot test that involved 30 unskilled workers in a vehicle assembly plant. The participants were composed of young employees who had joined the selected company for less than three years and yet to obtain certification for their skills. The validation analysis revealed that the panel of experts was in agreement with the suitability of the developed CDIM for unskilled workers in order to improve their career competencies. The outcomes of the pilot test displayed that the objectives of each sub-module (Knowing-Why, Knowing-How, and Knowing-Whom) were successfully met. Therefore, this study ascertains that the developed CDIM is indeed suitable for unskilled workers, especially towards enhancing their career competencies